Pengaruh Ukuran Perusahaan, Profitabilitas, dan Leverage Terhadap Tax Avoidance - Febrianti, Rindi Antika; Pramiana, Omi (Journal of Culture Accounting and Auditing, 2024)
This study examines the influence of firm size, profitability, and leverage on tax avoidance practices in coal companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2022. Tax avoidance refers to the legal strategy employed by companies to minimize tax obligations by exploiting loopholes in tax regulations. While lawful, such practices often raise concerns due to their potential impact on state tax revenues. Using a quantitative approach, this research employs multiple linear regression analysis to evaluate data from 20 coal companies selected through purposive sampling. The independent variables in this study include firm size (total assets), profitability (Return on Assets/ROA), and leverage (Debt to Equity Ratio/DER), while tax avoidance is measured using the Effective Tax Rate (ETR). The findings of this research are expected to provide insights into the determinants of tax avoidance and contribute to policymaking in the context of corporate tax regulations, particularly within the coal mining sector. Keywords: Firm Size, Profitability, Leverage, Tax Avoidance, Coal Companies